PMAQ-AB as a tool for public governance in health: Experience report care management in the territory - Cardoso, Carine dos Santos; Watanabe, Melissa; Camilo, Silvio Parodi Oliveira; Ferraz, Fabiane (Seven Editora, 2024)
Considering the assumptions of public governance and the importance of achieving greater effectiveness in health services, from 2011 to 2019 the federal government developed the National Program for Improvement of Access and Quality of Primary Care (PMAQ-AB), whose proposal was to promote expanding access and improving the quality of Primary Health Care, with greater transparency and effectiveness of actions according to the particularities of each location. The present work aims to report the experience about how adherence to PMAQ-AB occurred in a small city in southern Santa Catarina, expressing the benefits achieved and how this proposal is linked to the assumptions of public health governance. Based on the theoretical support of public governance and public governance in health, it became possible to conclude that the PMAQ-AB, when implemented and implemented in the municipality, proved to be an important tool for the institution of public governance principles, especially when dealing with the improvements provided at the local level, including the computerization of work processes,  the acquisition of vehicles and the remuneration for performance of public agents involved in the program, providing greater involvement and accountability, efficiency in the provision of services and greater capacity to respond to citizens. DOI:https://doi.org/10.56238/sevened2024.014-021